Українська та словенська національні ідеї у ХХ ст.: порівняльний аналіз - Мальшина, К.В.; Сінкевич, Є.Г.; Перовшек, Ю. (Український історичний журнал, 2015)
Порівнюються процеси державо- й націєтворення в Україні та Словенії в контексті розвитку національної ідеї. Зазначається про спільність історичних
процесів на українських і словенських землях у кордонах Австро-Угорської імперії, а також про хронологічну та змістову подібність шляху країн до самостійності. Звернуто увагу на фактори формування словенської національної
ідеї в умовах панування ідеології юґославізму. This article deals with the development of the national idea by comparing the proces-
ses of state-building and nation-building in Slovenia and Ukraine. The common
historical
processes in the Ukrainian and Slovenian lands within the borders of the
Austro-Hungarian Empire are concerned, as well as chronological and content similarity
of historical processes towards independence in both countries during this period.
The social processes, stages, moving forces, forms, methods, the fate of some participants
of the national liberation struggle of both peoples are researched. The factors of
formation of Slovenian national idea in conditions of the prepotency of the yugoslavism are described.